Prevalence, Beliefs, and the Practice of the Use of Herbal and Dietary Supplements Among Adults in Saudi Arabia: An Observational Study - Wajid Syed Msc Pharm; Osama A. Samarkandi PhD; Ahmed Al Sadoun PhD; Adel S. Bashatah PhD; Mahmood Basil A. Al-Rawi PhD; Mohammad K. Alharbi PhD (SAGE Publishing, 2022)
Background and Aim: Alternative treatments for respiratory disorders attempt to prevent or relieve symptoms and enhance functions. Furthermore, substantial evidence shows that several herbal medicines have been clinically effective against respiratory disorders. Thus this study assesses the Saudi students' use, beliefs, and practices related to herbal and dietary supplements for the possible prevention of respiratory infections. Methods: A cross-sectional web-based survey was designed using Google Forms to collect the data from the healthcare and non-healthcare students currently pursuing their courses at King Saud University, Riyadh, Saudi Arabia. The data was collected over 4 months, from November 2021 to February 2022, using convenience sampling with a 25-item questionnaire. A statistical package for social sciences, SPSS 26, was used to analyze the data. Results: A total of 274 participants responded to the study. The mean age of the respondents was 21.9 ± 3.08 (mean (SD)). The prevalence of herbal medicine (HM) was found to be 62.7% (n = 172). Around 48.5% (n = 133) of the respondents occasionally used some form of HM during the period of an illness associated with a respiratory infection. About 66% of the respondents agreed that using HMs prevents or controls respiratory symptoms and strengthens immunity. A majority (75.2%) of the respondents agreed that ginger extract possesses antiviral and immunity-boosting properties, followed by garlic extract (59.5%), cinnamon (39.4%), and lemongrass (38.3%). In addition, between 37% and 45.6% of the respondents agreed that vitamin C and vitamin D intake helps in boosting immunity and reducing the likelihood of developing respiratory infections. The overall mean of the positive beliefs and practice score was 9.6 (range 0-14). The mean positive beliefs and practice scores were significantly higher for males (11.4 ± 3.2) compared to females (8.6 ± 3.6) (P < .001). The numbers were not significantly different regardless of the source of information (9.6 ± 3.5), respondents being in health colleges (8.9 ± 4.1) or non-health colleges (9.8 ± 3.7), them being previously or currently infected (9.7 ± 3.8), the absence of infection (9.7 ± 3.8), or the respondents possessing a history of chronic diseases (10.5 ± 3.9) or not (9.5 ± 3.7) (P > .05). Conclusions: This study found a relatively high prevalence of herbal and dietary supplements' use, positive beliefs, and practices to strengthen one's immunity against respiratory symptoms.